EFFECT OF FeCl3 COAGULAN DOSAGE ON DECREASING TURBIDITY OF LEATHER TANNERY WASTE PROCESSING - Nanda Brilian Tantri; Swatika Juhana; Ragil Yuliatmo (Politek ATK Yogyakarta Press, 2023)
The leather tanning industry is one of the industries that produces liquid waste. The liquid waste of the leather tanning industry contains pollutants with a high level of turbidity. This research was conducted to determine variations in the dose of FeCl3 as a coagulant to reduce the turbidity of leather tanning wastewater. The coagulant added was 5 mL of FeCl3 with various doses of 1%, 2%, 3%, 4% and 5%. The optimum dose of FeCl3 coagulant to treat 300 mL of liquid waste is 3% with a volume of 5 mL, which means that 500 mg/L or 500 ppm is needed. The results showed a decrease in turbidity at the optimum dose was 94%, a decrease in chromium content of 83,53%. This shows that the effect of FeCl3 on reducing total chromium content and turbidity gives quite good results.